2008
DOI: 10.1007/s10554-008-9300-x
|View full text |Cite
|
Sign up to set email alerts
|

Delayed enhancement cardiac magnetic resonance imaging reveals typical patterns of myocardial injury in patients with various forms of non-ischemic heart disease

Abstract: Distinct LHE patterns exist in various NIHDs and their visualization may ultimately aid diagnosis. Unlike in ischemic heart disease, the structure-function relationship does not appear to be strong.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(72 citation statements)
references
References 41 publications
2
70
0
Order By: Relevance
“…Through these studies some patterns were identified that were related to certain non-ischemic disorders [1][2][3][4][5] . The aim of our study was to provide a structured approach in LGE analysis, which might be helpful in confining and arriving at the correct diagnosis, enabling appropriate treatment of non-ischemic diseases, thereby possibly reducing morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through these studies some patterns were identified that were related to certain non-ischemic disorders [1][2][3][4][5] . The aim of our study was to provide a structured approach in LGE analysis, which might be helpful in confining and arriving at the correct diagnosis, enabling appropriate treatment of non-ischemic diseases, thereby possibly reducing morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Late gadolinium enhancement (LGE) is a substantial part of CMR and is highly valued in both differentiating between ischemic and non-ischemic myocardial disease as shown by various studies [1][2][3][4][5][6][7][8][9][10][11] as well as identifying primary or secondary cardiomyopathy. LGE uses extracellular paramagnetic, Gadolinium-based contrast agents and reflects edema, myocyte necrosis or fibrosis of different etiologies.…”
Section: Introductionmentioning
confidence: 99%
“…There are predilection patterns of CE in patients with hypertrophic cardiomyopathies: more than 80% of patients exhibit patchy fibrosis at the right ventricular insertion points and in the anteroseptal wall in the region of characteristic septal thickening ( Figure 5ab; Figure 6a) (Moon et al, 2003;Choudhury et al, 2002). Myocardial fibrosis, however, is also located in non-hypertrophic segments (Bohl et al, 2008). As the amount of CE in hypertrophic cardiomyopathies often corresponds with functional parameters and the frequency of cardiac events, CE-CMR may potentially be useful for risk stratification and selection for implantable cardioverter defibrillator implantation (Rubinstein et al, 2010).…”
Section: Ce-cmr In Nonischemic Cardiomyopathies 321 Hypertrophic Camentioning
confidence: 99%
“…Myocardial fibrosis in idiopathic dilated cardiomyopathy is mostly seen in the left ventricular midwall with septal predominance and a linear pattern (Figure 5c,d; Figure 6b); however, it has occasionally been described at subendocardial and subepicardial locations with a more patchy pattern. (Bohl et al, 2008). Of note, in various studies the prevalence of myocardial fibrosis varied from 13% to 62% Isbell et al, 2006).…”
Section: Idiopathic Dilated Cardiomyopathymentioning
confidence: 99%
“…Focal myocardial late gadolinium enhancement is found in the specific cardiomyopathies, and the pattern is distinct from that seen in myocardial infarction, recent studies have demonstrated right ventricular late gadolinium enhancement in patients with congenital heart disease and right ventricular loading conditions [14,23]. Myocardial preservation is likely a multifactorial process that may affect the right and left ventricles differently [24][25][26][27][28].…”
mentioning
confidence: 99%